Burkitt’s lymphoma masquerading as appendicitis – two case reports and review of the literature - Weledji, Elroy P (BioMed Central, 2014)
Two cases of Burkitt’s lymphoma masquerading as appendicitis are reported herein. The diagnoses were made post-operatively from the appendix specimen in one case and from an ileocecal resection specimen for cecal fistula complicating an appendicectomy in the second case. These cases highlight the importance of routine histological examination of appendicectomy specimens.